Indira Gandhi: The Relationship between Personality Profile and Leadership Style - Blema S. Steinberg (Political Psychology, Vol. 26, No. 5, 2005, 2005)
This article explores the relationship between Indira Gandhi's personality profile in the period before she became Prime Minister and her leadership style during the time she was Prime Minister. The instrument for assessing the personality profile was compiled and adapted from criteria for normal personality types and pathological variants. Gandhi emerges as a multifaceted individual with four of her personality scales-the Ambitious, the Reticent, the Contentious, and the Dominating-approaching the level of mildly dysfunctional. A psychodynamic explanation for these patterns was then offered. This study also developed an instrument for evaluating leadership styles in a cabinet system of government and postulated the theoretical links between personality patterns and leadership style profiles. Gandhi's leadership style was then examined and links between personality profile and leadership style explored: In eight of the 10 leadership categories, Indira Gandhi's leadership behavior matched our expectations for the Ambitious, Dominant, and Contentious personality profiles but not the Reticent one. Further discussion focused on the two areas in which personality patterns fell short of predicting leadership style and the possible explanations for this result